A rare case of carbimazole induced severe aplastic anemia with fatal outcome - L, Naveen; Malkarnekar, Santoshi; S, Prathima (International Journal of Pharmacology and Toxicology, 2013)
Though agranulocytosis is a well known adverse effect of antithyroid drugs ( ATDs), aplastic anemia is thought to be rare. Herein we present a case report of carbimazole induced aplastic anemia in a patient of Grave’s disease, who satisfied all the criteria for severe disease and had profound bone marrow hypoplasia. Drug induced aplastic anemia is thought to be a result of an idiosyncratic response directed against hematopoietic stem cells and is managed in a similar fashion to idiopathic aplastic anemia. The hematopoietic  damage in our patient did not recover following ATD withdrawal and supportive treatment. This necessitated the use of immunsuppressive therapy with cyclosporine and antitymocyte globulin, which she could not afford and despite of all the supportive treatment she eventually succumbed to severe sepsis. Since ATDs are commonly used in clinical practice, the physicians should be aware of this rare but life-threatening complication.